The factors influencing self-management in patients with depression: a qualitative research from China - Ying-Li Gao; Lu-Xia Shen; Xiu-Mei Hou; Shu-Ping Si; Huan-Huan Zhu; Zhong-Li Shi (BMC Psychiatry)
Abstract Background As depressed patients often fail to seek help and obtain treatment on time for reasons such as stigma and lack of treatment resources, research on self-management for depressed patients is crucial. This study aimed to explore the factors influencing self-management in depression patients from the perspectives of both patients and psychiatric nurses. Methods Six depression patients and twelve psychiatric nurses were chosen for semi-structured interviews through a purposive sampling method from a tertiary Grade A psychiatric hospital in Shandong Province, China. The group of depressed patients included in the study had a male to female sex ratio of 1:1 with a mean age of 46years. The psychiatric nurse group had a male to female ratio of 1:2 with a mean age of 42.42 years. We used descriptive qualitative research techniques. Nvivo 12.0 software was used for the data management and analysis using thematic analysis. Results The factors influencing the self-management of depression patients were summarized into three themes and eight sub-themes: disease impact (symptoms, stigma), the degree of symptom control (medication adherence, depression’s cognitive status, its treatment and rehabilitation as well as additional factors), and support (self-efficacy, external support). Conclusions This study found that multiple factors influence the self-management of depression patients, including disease impact, the degree of symptom control, and support. In addition to helping patients integrate social resources and seek social support, medical staff should also pay attention to changes in the patient’s condition and disease control. Moreover, they should help patients increase their self-efficacy and enhance their self-management abilities through health education and other means. Clinical trial number Not applicable.